Infraphysiological 17β-estradiol (E2) concentration compromises osteoblast differentiation through Src stimulation of cell proliferation and ECM remodeling stimulus - Barneze Costa, Sarah Maria [UNESP]; da Silva Feltran, Georgia [UNESP]; Namba, Vickeline [UNESP]; Silva, Tabata Marilda [UNESP]; Shetty Hallur, Raghavendra Lakshmana [UNESP]; Saraiva, Patrícia Pinto [UNESP]; Zambuzzi, Willian Fernando [UNESP]; Nogueira, Celia Regina [UNESP] (Elsevier, 2020)
It has been shown that 17β-estradiol (E2) helps to prevent bone loss. This study was undertaken to verify whether E2 action in human osteoblasts involves changes in the transcriptional profile of the TNF-α, IFN-γ, NF-κB, TRAIL, TGF-β, MMP2, MMP9, RECK, TIMP1, TIMP2, CDK2, CDK4, SRC, RUNX2, and SHH genes. Infraphysiological doses of E2 elevated mRNAs in all genes except for INF-γ, TRAIL, and TGF-β. Importantly, a significant increase in the CDKs −2 and −4 genes was found, which strongly suggests cell cycle progression, with a potential dependency of Src involvement, as well as a suppression of the osteoblast differentiation machinery, with ECM remodeling being involved. These data suggest that E2 plays an important role in bone formation and remodeling, and Src seems to play a pivotal role in driving cell proliferation and ECM remodeling. Taken together, these findings contribute to an understanding of the effects of infraphysiological E2 on modulating bone homeostasis, favoring bone resorption, and leading to osteoporosis.
Keywords: Estrogen; Gene expression; Hormone; Mesenchymal stem cells; Osteoblast